2021
DOI: 10.46627/silet.v2i3.84
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Students’ Perceptions of Online Learning Environments on Students’ Satisfaction in the Context of Covid-19 Pandemic

Abstract: In the context of the Covid-19 pandemic, the present study aimed to examine students’ perceptions of online learning environments and students’ satisfaction based on their academic stream. The study also investigated the impact of students’ perceptions of online learning environments on students’ satisfaction. A quantitative descriptive survey method was applied. This study included 230 students (130 undergraduate and 100 postgraduate students) from colleges and universities of West Bengal. Online Learning Env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…Students can easily communicate with world Professors to share information and knowledge. This result is in line with literature review studies (Dastidar, 2021;Baber, 2020).…”
Section: Communication Opportunitiessupporting
confidence: 93%
“…Students can easily communicate with world Professors to share information and knowledge. This result is in line with literature review studies (Dastidar, 2021;Baber, 2020).…”
Section: Communication Opportunitiessupporting
confidence: 93%
“…Regarding the performance of the teacher in his e-teaching we contribute that 53% of the students respond that always or almost always the teacher performs his work of mentoring, of feedback with them, to improve their student performances and thus their university didactics is strengthened, with a new facet of the teacher in search The covid-19 pandemic, marked important milestones in university education, since many universities carried out their training of new professionals in person, and the current times with confinement of students and teachers is adopted by an asynchronous modality of studies, showing that the administration student is 85.2% is always or almost responsible for their punctual attendance at their virtual academic work, in the academic process of teaching classes, evaluations and other actions increasing academic satisfaction with responsibility and commitment, thus corroborating the conclusions of their research by Gelineau-Morel and Dilts (2021) Another significant result obtained is that the student states that online learning in 55.6% are always or almost always satisfied with what they have obtained from one semester to another from the 2020 academic year, and that they are important, which allows them to be used later in other subjects as well as strengthen their leadership skills, of decision-making and mentoring that would later lead him to use them in professional performance, findings that validate those obtained by Dastidar (2021) that in his research found differences in online learning and academic satisfaction of students, this is a contrast with what I conclude Carhuaz, 2020 where academic satisfaction is low in terms of students' online achievements.…”
Section: Results Discussionsupporting
confidence: 55%
“…In addition, a significant difference was found in their satisfaction with online learning environments according to academic current. Arts students scored the highest, while science students scored the lowest in their perceptions of online learning environments and satisfaction in online learning environments (Dastidar, 2021).…”
Section: Research Backgroundmentioning
confidence: 96%
“…The studies indicated that students experienced positive outcomes and that learning had a positive impact on their academic performance (Basith et al, 2020;Ngo et al, 2021). It can be predicted that online learning allows students to learn on their own and encourages self-discipline (Dastidar, 2021;Guo et al, 2022).…”
Section: The Students' Satisfaction With Online Learning During Covid...mentioning
confidence: 99%